Prostorsko planiranje in omrežje mest v Sloveniji - Gajšek, Miran (Urbani izziv, 2000)
The article presumes the development conjunction between urban centres and transport networks and presents the problem of urban development in connection with the development of transport infrastructure. Parallely runs a discussion on the nature of urbanity in the postindustrial society. Transport knots and enterprise zones are stressed as adequate and important elements of the contemporary settlement structure. The discussion is followed by categorisation of transport terminals, a review of conditions in the European union and an example of planning definitions from Great Britain. In conclusion ideas about the necessary connection between the spatial planning dimension and economic planning are emphasised.
Keywords: Europe; European Union; Evropa; Evropska unija; mesta; promet; prostorski razvoj; prostorsko planiranje; prostorsko urejanje; Slovenia; Slovenija; spatial planning